The influence of psychoemotional status on metastasis of lewis lung carcinoma and hepatocarcinoma-29 in mice of C57BL/6J and CBA/LAC strains - Kudryavtseva, N.N.; Tenditnik, M.V.; Nikolin, V.P.; Popova, N.A.; Kaledin, V.I. (Experimental Oncology, 2007)
Aim: To study the influence of psychoemotional status on the development of experimental lung metastases of strain-specific murine Lewis lung carcinoma in C57BL/6J mice and hepatocarcinoma-29 in CBA/Lac male mice. Materials and Methods: Sensory contact model was used for generating animals with repeated experience of social victories or defeat in daily agonistic interactions. Tumor cells were injected into the tail vein after 20 days of agressive confrontations and the number of metastases in the lung was calculated 16 days later. Results: The experimental metastasis is shown to develop differently in mice with opposing social experience: the winners of both strains had significantly less metastases in the lung than the losers. Conclusion: The results obtained indicate that psychoemotional status affects Lewis lung carcinoma and hepatocarcinoma-29 metastasis in male mice. Цель работы — исследование влияния психоэмоционального состояния на метастазирование линейноспецифических
опухолей — карциномы легкого Льюис у мышей линии C57BL/6J и гепатокарциномы-29 у мышей линии CBA/Lac.
Материалы и методы: для получения самцов мышей с повторным опытом социальных побед и поражений в ежедневных
агрессивных взаимодействиях была использована модель сенсорного контакта (на протяжении 20 дней). Клетки опухолей
вводили в хвостовую вену животных. Количество метастазов в легких подсчитывали через 16 дней после перевивки опухоли.
Результаты: показано, что метастазирование в легкие протекает неодинаково у мышей с различным психоэмоциональным
состоянием: у мышей с опытом побед обеих линий количество метастазов в легких было существенно меньше, чем у животных
с опытом психоэмоциональных поражений. Выводы: психоэмоциональное состояние влияет на процессы метастазирования
карциномы легкого Льюис и гепатокарциномы-29 у самцов мышей линий C57BL/6J и CBA/Lac.